Indicators and effectiveness of sensory and motor blocking unilateral spinal anesthesia combined with unilateral epidural analgesia (Eurasian Medical Research Periodical, 2022)
The relevance of this issue is due to the intensive development and introduction of the latest technologies in modern surgical interventions, including joint replacement, and a significant expansion of indications for surgical treatment. We have already pointed out that in the vast majority of patients of these operations, elderly and senile people with various comorbidities and, in some cases, severely disabled, burdened with severe pain for many months and years, which leads to whole complexes of somatic reactions. and deviations in the clinical status of patients. All this greatly complicates the choice of the method of anesthesia and postoperative analgesia. After all, postoperative pain is the result of surgery, but its treatment is not just a humane requirement, but a key aspect of postoperative therapy